THE EVALUATION OF LEVEL COMMERCIALIZATION OF THE RESULTS OF SCIENCE AND TECHNOLOGY ACTIVITIES - Svetlana A. Finashina (Вестник Северо-Кавказского федерального университета, 2022)
The paper presents the main provisions of methodology to determine the degree of commercialization of an innovative company focused on the application in the subjects of small business. The results of its approbation are presented.